Nature's Role in the Experience of Digital Nomads: The Town of Bansko as a Case Study (Seminar_BG, 2025)
This article presents the results of a series of field studies on digital nomadism in Bansko—a resort town that has been an established meeting point for digital nomads from all over the world for a decade. This form of mobile lifestyle is characterized by the frequent and repeated crossing of national borders by mobile individuals (digital nomads), who stay for varying lengths of time in different countries and do not return permanently to their home country According to them, Bansko is unique because it offers natural resources, infrastructure that enables remote work, and a community of like-minded people. What prompts these individuals to settle for extended periods in a small town like Bansko, and why is it crucial for them to be close to nature (to create and work undisturbed, away from the overstimulation typical of big cities; to raise their children in a peaceful environment, etc.)? What are the dimensions of nature within the urban environment (playing in yards and mountain streams flowing along the streets; organizing community-building outdoor events; incorporating natural materials into the interior and exterior of spaces inhabited by digital nomads, etc.)?References Bell, D. (2006). Variations on the Rural Idyll. In P. Cloke, T. Marsden, & P. Mooney (eds.), Handbook of Rural Studies (pp. 149–160). London: Sage. doi.org/10.4135/9781848608016.n10Bunce, M. (2003). Reproducing Rural Idylls. In P. Cloke (ed.), Country Visions. Harlow: Pearson.Cook, D. (2023). What is a digital nomad? Definition and taxonomy in the era of mainstream remote work. World Leisure Journal, 65(2), 256–275. doi.org/10.1080/16078055.2023.2190608Dimitrova, P. (2025). Digitalno nomadstvo: kulturni transformatsii, sotsialni dinamiki i predizvikatelstva v Bansko. Sofia: IEFEM – BAN [forthcoming].Dimitrova, P. (2025). New age kultura i layfstayl migratsiya ot grad kam selo: primeri ot vseкидnevieto na edna obshtnost. Balgarska etnologiya, 1, 86–102.GRAO. (2023). Tablitsa na adresno registriranite po postoyanen i po nastoyasht adres litsa v oblast BLAGOEVGRAD obshtina BANSKO. https://www.grao.bg/tna/isnt41nm-15-09-2023-2.txt [15.12.2025].Kastels, M. (2006). Informatsionnata epoha: ikonomika, obshtestvo i kultura, t. II, Silata na identichnostta. Sofia: LIK.Kozinets, R. (2015). Netnography: Redefined. London: Sage. doi.org/10.1002/9781118767771.wbiedcs067Kyurkchiev, S. (2019). Psihologicheski ekspertizi i grizhata za sebe si. Sofia: Iztok-Zapad.Makimoto, T., & Manners, D. (1997). Digital nomad. Chichester: Wiley.Miller, D. (2023). The Good Enough Life. Cambridge: Polity Press.Modi, Priyanka. 2023. Bansko Families Foster Outdoor Learning: Creating Classrooms in the Forest. Educationnext. https://educationnext.in/posts/bansko-families-foster-outdoor-learning-creating-classrooms-in-the-forest [22.12.2025]Molz, J. (2021). The World Is Our Classroom: Extreme Parenting and the Rise of Worldschooling. New York: New York University Press. doi:10.18574/nyu/9781479891689.001.0001Obshtina Bansko. (2023). Naredba za spetsifichni iziskvaniya kam oblika na gradskite prostranstva, sgradite i arhitekturnite ansambli na teritoriyata na grad Bansko.Orel, M. (2019). Coworking environments and digital nomadism: balancing work and leisure whilst on the move. World Leisure Journal, 61(3), 215–227. http://dx.doi.org/10.1080/16078055.2019.1639275 Orel, M. (2023). Wanderlust workforce: a journey into understanding digital nomadism. World Leisure Journal, 65(2), 143–149.Pacheco, C., & Azevedo, A. (2022). Mapping the journey of the CoLiving experience of digital nomads, using verbal and visual narratives. World Leisure Journal, 65(2), 192–217. doi:10.1080/16078055.2022.2156593 Radonova, M. (2018). V podnozhieto na Perun. Sofia: Zahariy Stoyanov.Šímová, T. (2023). A research framework for digital nomadism: a bibliometric study. World Leisure Journal, 65(2), 175–191. doi.org/10.1080/16078055.2023.2210017Soper, K. (2020). The Post-Growth Living. London: Verso.Toivanen, M. (2025). The Freedom Paradox: Meanings and Configurations of Digital Nomadic Work. International Migration Review, 60(1), 22-45. doi:10.1177/01979183251314848Vogl, T., & Micek, G. (2023). Work-leisure concepts and tourism: Studying the relationship between hybrid coworking spaces and the accommodation industry in peripheral areas of Germany. World Leisure Journal, 65(2), 276–298. doi.org/10.1080/16078055.2023.2208081Voll, K., Gauger, F., & Pfnür, A. (2022). Work from anywhere: Traditional workation, coworkation and workation retreats: A conceptual review. World Leisure Journal, 65(2), 1–25. https://doi.org/10.1080/16078055.2022.2134199Woldoff, R. A., & Litchfield, R. C. (2021). Digital nomads: in search of freedom, community, and meaningful work in the new economy. New York: Oxford University Press.Zumbusch, J., & Lalicic, L. (2020). The role of co-living spaces in digital nomads’ well-being. Information Technology & Tourism, 22, 439–453. doi:10.1007/s40558-020-00182-2
Keywords: digital nomadism; nature; Bansko; worldschooling